If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(3 + 4x) + -2 = 58 (3 * 4 + 4x * 4) + -2 = 58 (12 + 16x) + -2 = 58 Reorder the terms: 12 + -2 + 16x = 58 Combine like terms: 12 + -2 = 10 10 + 16x = 58 Solving 10 + 16x = 58 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 16x = 58 + -10 Combine like terms: 10 + -10 = 0 0 + 16x = 58 + -10 16x = 58 + -10 Combine like terms: 58 + -10 = 48 16x = 48 Divide each side by '16'. x = 3 Simplifying x = 3
| 5x^6-3x^3+1=0 | | 3(4x+7)=-47+8 | | 3(x-2)=3(x-2)+6 | | 7x^2-10xy+3y^2=0 | | 7x+13=5x+7 | | -(5x+1)=-7x+3 | | 15-x=-12 | | 9x^2-21xy-18y^2=0 | | .25w+4=-3(.25w+2)+8 | | -(6y+4)-(-5y-6)=-2 | | 8(5+4)= | | -3x+21=3x-21 | | x^4-10x^2-96=0 | | -50z-0.2=-60z+1.4 | | 8n-(3n+8)=32 | | -6y-1=5y-2 | | -[8x-(2x+7)]=1-(9x+3) | | 12+33=-5(2x-9) | | 3(7-x)-33=21x-4(3+6x) | | -8-(-n)=1 | | 8+24=-4(6x-8) | | -175=-29x-30 | | 2x^3-2x+9x^2-24x=0 | | 12x-3=24+5 | | 5x(4x+45)=360 | | -175=-29-30 | | 8n-(6n+7)=1 | | 2x^3-2x+9x^2-24=0 | | (t-1)(t+2)=0 | | 4(3x+9)=-31+7 | | 2/3-6h=13/6 | | -6x^2+15x=0 |